ANALISIS STRATA NORMA PUISI “SEBAB DI KAU” DITINJAU DARI SEGI LAPIS DUNIA DAN LAPIS METAFISIS KARYA AMAR HAMZAH - Taufik Taufik; Susiati Susiati; Novita Sari P. Masuku (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
Poetry can be viewed from various aspects, including the strata of norms, semiotics, the meaning of class, and so on. The purpose of this research is to describe the form of the poetry "sebab dikau" based on norm literature in terms of layers of the world and metaphysical layers and reveal the meaning contained in the poetry. This research uses the literature method. The data in this study were verbal in the form of words contained in the poetry "sebab dikau" by Amir Hamzah. The results showed that the poetry "sebab dikau" by Amir Hamzah was formed by 5 stanzas. Each verse consists of 4 lines. So, the total of the whole poetry consists of 20 lines. The first verse rhymes ab-aa, the second stanza rhymes ab-ab, the third stanza rhymes ab-ab, the fourth stanza rhymes ab-aa, and the fifth stanza rhymes ab-ab. The first sound of alliteration, namely alliteration k is in verse I and V, alliteration m is in verse I, alliteration l is in verse II and III, alliteration t, s is in verse III, alliteration g is in verse IV. Furthermore, the sound of romance a is found in verses I, III, and IV, the sound of annoyance i is in verse II, the sound of annoyance u is in verse II and verse III, the sound of annoyance e is found in verse IV and verse V. In the analysis of the poetry, I showing pleasure to the girl or lover, who gives all hope to life. In my heart, I grow in love and bloom like a fragrant flower that feels to the core. But my life feels like a dream, like the puppets on the screen and then he realizes that life is only brief. In essence, theme and his lover are a (thee) puppet that pleases the mastermind who plays humans like puppets. Keywords: alliteration, assonance, stanza, lines